Insights into the chemical characteristics of melted snow from urban-industrial sites: case study of Starachowice (Poland) - Szwed , Mirosław; Kozłowski, Rafał; Ludew, Marta (Acta Geographica Lodziensia, 2025)
This study analyses the chemical composition of snow cover in Starachowice, an industrial city in south-eastern Poland, to assess the extent and sources of atmospheric pollution. The research confirms the accumulation, in snow, of partic-ulate pollutants that act as carriers of heavy metals. The analysis confirmed increased pH of water from the melted snow samples (pH 6.99) and significantly increased concentrations of Fe (110.96 μg/dm3), Al (85.02 μg/dm3), Zn (43.68 μg/dm3) and Mn (10.92 μg/dm3) in relation to the properties of snow precipitation observed in the Świętokrzyski National Park. The spatial variability of the analysed metals was demonstrated. The lowest values were found in the central part of the study area, in the immediate vicinity of a metal production plant, while the highest values were recorded near the metal processing plant in the southern part of the study area. The presence of particles of various shapes and chemical composition was confirmed using Scanning Electron Microscopy/Energy Dispersive X-ray Spectroscopy (SEM/EDS) analyses of the glass filter used for filtering meltwater. The image showed the presence of larger sharp-edged particles and smaller spherical particles (spher-ules) with a significant share of Al, Mg and Fe. The study highlights the role of industrial activity in atmospheric contamination and emphasises the need for stringent air quality monitoring and control.